Influences of Structural Relaxation and Crystallization on Dry-Sliding Tribological Behavior of Fe-Based Amorphous Coating - Kang, Yonghai; Chen, Youming; Yan, Chengqi; Kong, Lingqian (Tribology letters, 2021)
Fe-based amorphous coatings have promising applications in the field of surface protection. However, due to their brittle characteristics, delamination has become the most common wear mechanism of the coating. In present study, influences of structural relaxation and crystallization on microstructure, hardness and dry-sliding tribological behavior of the coatings are investigated. The results indicate that wear resistance of the coating could be enhanced by structural relaxation, although there is no obvious change of the hardness. Hardness of the coating increases obviously after crystallization due to the massive formation of brittle crystals, however, the coating only exhibits lower wear rate under lower applied load, but the wear rate increases drastically with applied load because brittle crystals increase brittleness of the coating and cause severe delamination of the coating under higher applied loads.